tan θ +sin θ ÷tan θ -sin θ =sec θ +1÷sec θ -1
Answers
Answered by
12
Hello !
Question:-
=
given:-
- L.H.S =
- R.H.S =
Proof :-
Refer to the attachment.
Don't mention, sure, would love to be ur frnd❤️
Attachments:
![](https://hi-static.z-dn.net/files/dab/929ab72ce977eb8735371a8a93d40ced.jpg)
Answered by
13
Step-by-step explanation:
Hello !
Question:-
\dfrac{tanA+SinA}{tanA-SinA}
tanA−SinA
tanA+SinA
= \dfrac{SecA+1}{secA-1}
secA−1
SecA+1
given:-
L.H.S = \dfrac{tanA+SinA}{tanA-SinA}
tanA−SinA
tanA+SinA
R.H.S = \dfrac{SecA+1}{secA-1}
secA−1
SecA+1
Plz Drop Some Thx please
Similar questions